Conversion of agonist site to metal-ion chelator site in the β(2)-adrenergic receptor - Elling, Christian E. (The National Academy of Sciences, 1999)
Previously metal-ion sites have been used as structural and functional probes in seven transmembrane receptors (7TM), but as yet all the engineered sites have been inactivating. Based on presumed agonist interaction points in transmembrane III (TM-III) and -VII of the β(2)-adrenergic receptor, in this paper we construct an activating metal-ion site between the amine-binding Asp-113 in TM-III—or a His residue introduced at this position—and a Cys residue substituted for Asn-312 in TM-VII. No increase in constitutive activity was observed in the mutant receptors. Signal transduction was activated in the mutant receptors not by normal catecholamine ligands but instead either by free zinc ions or by zinc or copper ions in complex with small hydrophobic metal-ion chelators. Chelation of the metal ions by small hydrophobic chelators such as phenanthroline or bipyridine protected the cells from the toxic effect of, for example Cu(2+), and in several cases increased the affinity of the ions for the agonistic site. Wash-out experiments and structure–activity analysis indicated, that the high-affinity chelators and the metal ions bind and activate the mutant receptor as metal ion guided ligand complexes. Because of the well-understood binding geometry of the small metal ions, an important distance constraint has here been imposed between TM-III and -VII in the active, signaling conformation of 7TM receptors. It is suggested that atoxic metal-ion chelator complexes could possibly in the future be used as generic, pharmacologic tools to switch 7TM receptors with engineered metal-ion sites on or off at will.